Legal Analysis of Acts of Default in Cooperation Agreements (Case Study of Decision Number 48/Pdt.G/2020/PN.Idm) - Audrey Bintang Silado (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The agreement was born because of agreements between the parties, which gave rise to rights and obligations for the parties involved. Every agreement that is made always aspires that what is agreed upon can run as it should, but in practice there are often broken promises between the parties or what is known as default. Default is a situation where one of the bound parties is negligent or does not fulfill the obligations set out in the agreement. A debtor is declared in default if: does not do what is agreed upon in the agreement, carries out what was promised but is not in accordance with the agreement, does something that cannot be done in the agreement. In the case of the cooperation agreement between Plaintiff Puji Riyanto and Defendant I Susi Suryani and Defendant II Atoillah Dalil, this cooperation agreement was deemed to have defaulted where the defendants neglected to return the capital money and profits for the cooperation agreement to make Alfamart franchise stores. The purpose of writing this journal is to find out the consequences of default according to the Civil Code and legal settlement efforts for default. The writing method used in this paper is normative juridical. The legal consequences of default are cancellation of agreements, compensation, transfer of risks and paying court fees. Legal settlement efforts for acts of default are means of preventive and repressive legal protection.